Brief Analysis of the Cross-Cultural Communication of K-pop and its Industry in the US from the Perspective of the Theories of Interculturality - Jin, Xiaoqi (International Journal of Social Sciences and Public Administration, 2025)
This research explores how the K-pop industry has utilized cross-cultural communication strategies to expand its influence in the United States, employing the theoretical lens of interculturality. By examining the evolution of K-pop, its global marketing tactics, and its cultural assimilation into the U.S. market, the study highlights the industry’s nuanced approach to language, music styles, visual representation, and tailored market strategies. The analysis reveals unique cross-cultural elements of K-pop, including the creation of a “third space,” the resolution of cultural tensions, the redefinition of identities, and the fostering of cultural synergy. These aspects establish K-pop as a notable and effective model for cross-cultural communication.